Temporal trends in prevalence and years of life lived with disability for hearing loss in China from 1990 to 2021: an analysis of the global burden of disease study 2021 - Sun, Yuhuan; Yi, Yang; Huang, Geyao; Jiang, Shihao; Zhou, Yuchen; Chen, Hongkun; Wang, Dahui (Frontiers in Public Health, 2025)
BackgroundHearing loss (HL) poses a serious threat to the health and quality of life of Chinese population. This study analyzes the burden of HL in China from 1990 to 2021 and projects future trends in next 15 years.MethodsData derived from the Global Burden of Disease (GBD) 2021 study were utilized. The join-point regression model was employed to calculate the average annual percentage change (AAPC) in the prevalence and years of life lived with disability (YLDs) of HL. Age-period-cohort analysis was conducted to assess age, period and cohort effects. Decomposition analysis was performed to analyze the impacts of aging, population and epidemiological change. ARIMA model was utilized for forecasting the burden of HL from 2022 to 2036.ResultsFrom 1990 to 2021, the number of prevalence and YLDs of HL in China rose by 125.06 and 135.13%, with an average annual percentage change of 0.19 and 0.28% for age-standardized rate (ASR) of prevalence and YLDs, respectively. Age-period-cohort analysis indicated that the risks associated with ASR of prevalence and YLDs for HL increased with age. The period effects on the ASRs of prevalence and YLDs were generally increasing (relative risk [RR] 0.98–1.06 and 0.96–1.05). Cohort effects on the risk also rising (RR 0.90–1.41 and 0.83–1.26). Aging growth accounted for the largest proportion of the increase of the number of prevalence and YLDs (68.62 and 66.39%, respectively). The prevalence and YLDs rates are expected to stabilize from 2022 to 2036, while the age-standardized prevalence rate remains above 20%. The number of people suffering from HL will reach 573.8 million, while the number of YLDs will reach 16 million.ConclusionThe prevalent cases of HL have risen dramatically in China over the past 32 years, which expected to continue to grow by 2036, additional interventions such as enhancing primary hearing care services and boosting screening rates for HL are essential to alleviate the burden of HL, especially in the older adult population.